(untitled) (Research, Society and Development, 2023)
The hospitalization for mental and behavioral disorders are still seen as a condition of a dysfunctional individual, this is a inheritance of the first psychiatric hospitals, also called asylums. With the changes in the field of health in Brazil, there were reformulations in the management of mental disorders. This work aimed to outline a epidemiological profile about the hospitalization for mental and behavioral disorders in the municipality of Cascavel/PR from 2015 to 2021 and compare data in Brazil’s level. This is a descriptive and quantitative study, the data were collected from hospital information system (SIH/SUS) on the internet platform DATASUS, covering data of hospitalizations and hospital morbidity. As a result, it was shown that men, white people and between the ages of 30 and 49 years have higher rates of hospitalization. These data are similar at the country level. Regarding hospitalizations, it was evidenced that the municipality of Cascavel had 1261 hospitalizations in the period, which corresponds to 0.08% of hospitalizations in the Brazilian territory. The average stay had its highest index in the year 2015 with 40.6 days, and the lowest in 2017 with 27.5 days. Regarding deaths, there were 2 in the municipality, while in Brazil, 8,138, in the same period. It was evident that Cascavel’s expenses correspond to 0.1% of Brazilian expenses.